The liberation of Jerusalem = (Gerusalemme liberata) - Tasso, Torquato, 1544-1595.; Wickert, Max; Davie, Mark (Oxford ; New York : Oxford University Press, 2009)
"In The Liberation of Jerusalem (Gerusalemme liberata, 1581), Torquato Tasso set out to write an epic to rival the Iliad and the Aeneid. Unlike his predecessors, he took his subject not from myth but from history: the Christian capture of Jerusalem during the First Crusade. The siege of the city is played out alongside a magical romance of love and sacrifice, in which the Christian knight Rinaldo succumbs to the charms of the pagan sorceress Armida, and the warrior maiden Clorinda inspires a fatal passion in the Christian Tancred. Tasso's masterpiece left its mark on writers from Spenser and Milton to Goethe and Byron, and inspired countless painters and composers. This is the first English translation in modern times that faithfully reflects both the sense and the verse form of the original. Max Wickert's fine rendering is introduced by Mark Davie, who places Tasso's poem in the context of his life and times and points to the qualities that have ensured its lasting impact on Western culture" --
Introduction; A Note on the Translation; Select Bibliography; A Chronology of Torquato Tasso; THE LIBERATION OF JERUSALEM; Appendix: Tasso's Liberation of Jerusalem in Literature, Art, and Music; Explanatory Notes; Glossary of Proper Names
Includes bibliographical references (pages xxx-xxxii).
Print version record.
eBooks on EBSCOhost
Keywords: Godfrey, -- of Bouillon, -- approximately 1060-1100 -- Poetry; Godfrey, -- of Bouillon, -- approximately 1060-1100; Jerusalem -- History -- Latin Kingdom, 1099-1244 -- Poetry; Epic poetry, Italian -- Translations into English; Crusades -- First, 1096-1099 -- Poetry; Jérusalem (Royaume latin, 1099-1244) -- Poésie.; Croisades -- 1re croisade, 1096-1099 -- Poésie.; POETRY -- Continental European; Crusades; Epic poetry, Italian; Middle East -- Jerusalem; 1096-1244; History; Poetry; Translations